The Transfer Effects of Cognitive Training on Working Memory Among Chinese Older Adults With Mild Cognitive Impairment: A Randomized Controlled Trial - Weng, Wenqi; Liang, Jiaming; Xue, Jiang; Zhu, Tingfei; Jiang, Yuxing; Wang, Jiayu; Chen, Shulin (Frontiers in Aging Neuroscience, 2019)
Objectives: To explore the transfer effects of cognitive training on working memory among Chinese older adults with mild cognitive impairment (MCI). Methods: 62 MCI participants aged more than 60 years old were recruited by holding recruitment sessions at communities in China (33 for cognitive training, and 29 for mental leisure activities (MLA) control). Cognitive functions, including working memory, execution function, reasoning ability, verbal ability, ability of daily living, were measured at 3 time-points (baseline, post-training and three months after training). Results: Compared to the MLA control, the cognitive training group showed significant effects on both the trained (working memory) and untrained (execution function and ability of daily living) domains. The effects of cognitive training on overall cognitive function, working memory and daily life ability of daily living of MCI could be maintained for at least three months even without the cognitive training. Besides, complete mediating effects of cognitive training were found on executive function through working memory and working memory on ability of daily living though executive function which suggested the presence of transfer effect of cognitive training. Conclusions: The present study supported that cognitive training could effectively improve working memory in elders with MCI. The training effects on working memory could transfer to other untrained areas (such as executive function), which also improved the comprehensive ability (ability of daily living). And the effects of training could largely persist for three months. Key Words: Mild cognitive impairment; Cognitive training; Working Memory; Transfer effects; Maintaining effect